Karakteristik Sensorik Telur Asin dengan Pemberian Tepung Daun Jeruk Purut (Citrus Hystrix) - Arifin, Ilmi; Ulfah, Triana; Adiputra, Rachmat; Hariadi, Hari; Akhdiyat, Tedi (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2024)
Eggs are a food ingredient with a relatively high protein content and have complete amino acids, unsaturated fats, vitamins and minerals that the body needs and are easy to digest. Eggs are always available throughout the year, but the fact is that egg shells crack easily, relative humidity and temperature in the storage room can affect the quality of eggs and cause chemical and microbiological changes so preservation efforts are needed to maintain the quality of the eggs. Salted eggs are a way to preserve eggs which has the benefit of improving the taste and the texture of the egg yolk. The addition of kaffir lime leaf flour is one of the diversification methods for processing salted eggs. The aim of this research was to determine the sensory characteristics of salted eggs by administering kaffir lime leaf flour. The experimental research used a Completely Randomized Design (CRD) with 5 treatments, namely S0: 0% kaffir lime leaf flour, S1: 15% kaffir lime leaf flour, S2: 20% kaffir lime leaf flour, S3: 25% kaffir lime leaf flour, and S4: 30% kaffir lime leaf flour with 5 repetitions. he results of the research showed that salted eggs with 25% kaffir lime leaf flour produced salted eggs that were liked by the panelists in terms of sensory characteristics.